The last battle of Alessandro Farnese (1545-1592): Some medical considerations regarding the health of the Renaissance leader who changed Europe - Armocida, Emanuele; Masciangelo, Graziella; Bussolati, Ovidio (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Alessandro Farnese (1545-1592), 3rd Duke of Parma and Piacenza, one of the most important generals and politicians of his age. He died after a rapid deterioration of his health. The available documents testify that the Duke suffered for a long time from various health problems, such as jaundice, intestinal disorders, gout, dropsy but very little is known about the cause(s) of his death. The aim of this article is to offer for the first time a complete clinical interpretation of Alessandro Farnese’s last months of lifeMethods: A collection of descriptions of symptoms and signs described by his court physician and by the leading biographers of Farnese has been compiled. This collected medical evidence has been interpreted in the light of current medical knowledge, to obtain a final interpretation.Results: The results led us to consider liver diseases, neoplastic diseases (especially pancres) and infectious diseases (including typhus and malaria) as causes or contributing causes of death.Conclusions: The accurate autopsy description, in association with the anamnestic information provided by the historical documents studied, suggests that Alessandro Farnese was a hepatopathic patient suffering from spontaneous bacterial peritonitis. In the pre-antibiotic era, the pathological organ alterations described certainly have at least contributed to making the infectious episode (that the autopsy describes of pulmonary origin) fatal.